The treatment of coronary artery aneurysm with a hybrid approach - Acipayam, Mehmet; Eroğlu, Erdinç; Yasım, Alptekin (The European Research Journal, 2020)
Coronary artery aneurysms (CAAs) are rare cases that generally present with ischemic symptoms. Although coronary artery bypass surgery is widely performed in treatment, endovascular procedures have also begun being used in recent years. We describe a patient developing acute myocardial infarction due to CAA at a young age, despite the absence of any risk factor, followed by rapidly growing aneurysm. This patient was treated with a hybrid approach, very rare case in the literature.